MEMBANGUN SUSTAINABILITAS (CONTINUOUS IMPROVEMENT) DALAM PENDIDIKAN - Moh Asvin Abdurrohman; Izzudin Rijal Fahmi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2021)
Management of educational quality improvement is the integration of all function and processes within an educational organization in order to achieve continuous improvement of the quality of school outputs and services. The main objective is the satisfactions of the clients or customers. The application of TQM in the context of educational organizations is based on a framework that educational managers are able to make the process of continuous improvement. Eventhough at the beginning TQM itself was used by the company or business sector but today has grown up and spread to the world of education. It is because basically, the management system between the company and the management of the education system is relatively the same, especially related to the primary goal of TQM that is to give priority to customer satisfaction and quality compared to other things. Thus, the quality of education is a key sector for TQM concepts to develop an institution variously, creatively and innovatively.